(untitled) - Snapp, Sieglinde S. (Amsterdam, 2008)
With the inclusion of research theory and examples using the principles of cropping system design, students will gain a unique understanding of the technical, biological, ecological, economic and sociological aspects of farming systems science for rural livelihoods. Editors Snapp and Pound provide a much-needed synthetic overview of the emerging area of agroecology applications to transforming farming systems and supporting rural innovation. The wide range of subjects, integrated references, and companion website, make this core reading for courses in international agricultural systems and management, sustainable agricultural management, and cropping systems.
Nguyên lý cơ bản hệ thống nông nghiệp
Keywords: Agricultural systems,Agricultural ecology,Sustainable development,Rural development,Phát triển nông thôn,Sinh thái nông nghiệp,Hệ thống nông nghiệp,Phát triển bền vững